Precursor concentration and temperature controlled formation of polyvinyl alcohol-capped CdSe-quantum dots - Shah, Chetan P.; Rath, Madhabchandra; Kumar, Manmohan; Bajaj, Parma N. (Beilstein Journal of Nanotechnology, 2010)
Polyvinyl alcohol-capped CdSe quantum dots, with a size within their quantum confinement limit, were prepared in aqueous solution at room temperature, by a simple and environmentally friendly chemical method. The size of the CdSe quantum dots was found to be dependent on the concentrations of the precursors of cadmium and selenium ions, as well as on the aging time and the reaction temperature; all of which could be used conveniently for tuning the size of the particles, as well as their optical properties. The synthesized quantum dots were characterized by optical absorption spectroscopy, fluorescence spectroscopy, X-ray diffraction, atomic force microscopy and transmission electron microscopy. The samples were fluorescent at room temperature; the green fluorescence was assigned to band edge emission, and the near-infrared fluorescence peaks at about 665 and 865 nm were assigned to shallow and deep trap states emissions, respectively. The quantum dots were fairly stable up to several days.
Keywords: cadmium selenide; electron microscopy; energy dispersive X-ray analysis (EDAX); semiconductor